2013
DOI: 10.1063/1.4825212
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-enhanced polarization imaging with focused thermal pulses

Abstract: The non-destructive measurement of electrical polarization and space charge densities is a key technique in electret research. The principal idea behind these methods is a non-uniform deformation or heating, which gives rise to a short-circuit current that can be recorded in the time or frequency domain, and which carries information about the polarization depth profile. In recent years, thermal pulses and thermal waves have been used successfully to obtain three-dimensional polarization maps in polymeric elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…[36][37][38][39][40][41][42] The first results showed that non-contacting measurements were possible, provided that significant currents can be extracted from noise. In this case, they are representative of an internal space charge (or polarization) in the sample that can be calculated by mathematical inversion of the electrostatic problem.…”
Section: B Application: 2-d and 3-d Cartographiesmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] The first results showed that non-contacting measurements were possible, provided that significant currents can be extracted from noise. In this case, they are representative of an internal space charge (or polarization) in the sample that can be calculated by mathematical inversion of the electrostatic problem.…”
Section: B Application: 2-d and 3-d Cartographiesmentioning
confidence: 99%
“…35 a metal-oxide-semiconductor (MOS) structure with thickness of several hundreds of nanometers was tested. The TPM has been recently adapted by Mellinger and Aryal for both 2D 36 and 3D measurements. 36,37 …”
Section: A the Thermal Pulse Methodsmentioning
confidence: 99%